Turn on your TAP: memory in language processing - Gabryś-Barker, Danuta (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
Memory has always constituted an important aspect of research on language acquisition and learning. Traditionally, this research looks at the processes involved in memorising language elements, that is, memory learning strategies in FL vocabulary acquisition or the processes involved in the recall of language, for example retrieval strategies. In descriptions of language processing, models created have highlighted ways of memory functioning at different stages of incoming data-processing, thus focusing on short term memory (STM) and long term memory (LTM) and the relations between the two. Individual learner differences at the level of cognitive styles have also been investigated in relation to memory as a significant variable in learning and language production. The above mentioned areas of research are most frequently investigated by means of different retrospective techniques. This paper is also concerned with language processing and the ways STM is activated but on this occasion simultaneously with exposure to a language task to be performed. The main objective of the paper is to demonstrate how simultaneous introspection as a research method can inform us about these processes and the functioning of memory. It looks at selected research projects using simultaneous introspection and think-aloud protocols (TAP-s) as ways of collecting and analysing data in a multilingual context of language production. The aim of the paper is not however to discuss the findings and to answer the research questions posed in my own research over the period 1993-2005 but to show the general validity of TAP data in studying memory and language activation processes.